THE ORGANIZATIONAL CULTURE OF THE REGIONAL CHILD PROTECTION COMMISSION (KPAD) OF PONTIANAK CITY IN SAFEGUARDING THE NATION’S YOUNG GENERATION - Riwayati, Anny; Auliya Rahma, Fatiya; Ester Elhani, Katri (Berumpun: International Journal of Social, Politics, and Humanities, 2025)
Over the past four years up to 2024, the Human Development Index (HDI) of Pontianak City has shown consistent improvement, indicating the local government's commitment to enhancing public welfare. Despite this progress, child abuse remains a serious concern, with 56 reported cases including psychological abuse and sexual violence in 2024 alone. This study aims to examine how the organizational culture within the Regional Child Protection Commission (KPAD) of Pontianak contributes to child protection efforts. A qualitative research method was employed to explore the dynamics of organizational culture and practices within KPAD. The findings indicate that KPAD maintains a flexible organizational culture to stay responsive to public complaints around the clock. Commissioner recruitment is conducted transparently through official website announcements to ensure the selection of qualified candidates. The organization upholds core values of independence, accountability, professionalism, and partnership. The study concludes that while KPAD has laid a strong foundation, further efforts are needed to strengthen communication with victims' families, expand public education campaigns, implement structured monitoring mechanisms, and regularly evaluate service quality to foster public trust and encourage transparent reporting.